Integration of Electrical Properties and Polarization Loss Modulation on Atomic Fe–N-RGO for Boosting Electromagnetic Wave Absorption - Kaili Zhang; Yuefeng Yan; Zhen Wang; Guansheng Ma; Dechang Jia; Xiaoxiao Huang; Yu Zhou (Nano-Micro Letters)
Highlights Single-atom Fe–N4 sites embedded into graphene were successfully synthesized to exert the dielectric properties of graphene. The absorption mechanisms of metal-nitrogen doping reduced graphene oxide mainly include enhanced dipole polarization, interface polarization, conduction loss and defect-induced polarization. Excellent reflection loss of − 74.05 dB (2.0 mm) and broad effective absorption bandwidth of 7.05 GHz (1.89 mm, with filler loading only 1 wt%) were obtained.